Possibilidades de ações colaborativas entre professores e coordenador pedagógico no projeto de formação de uma escola da rede municipal de São Paulo - Coelho, Talita da Cruz (2022)
This dissertation searches to analyze the boundaries of teachers' perceptions and engagement in the formative process, from the coordinator perspective in a public school of São Paulo council. The study followed the impact of the pandemic moment in São Paulo city council, and the implement of public policies to support remote education in public schools. It also followed the return of face-to-face learning between 2020 and 2021, and the teachers’ forming actions. The theoretical framework was guided in the study of Imbernón, Heargraves, André, Passos & André, Dugnani & Souza, Placco & Souza, Orsolon, Souza, Marcelo and Canário, about the continuing in-service teacher education, forms of participation and collaborative work between teachers’ group and pedagogical coordination. The study was carried out in a Municipal School of Elementary Education (EMEF), located in the northwest of São Paulo. The subjects were five elementary school teachers and one pedagogical coordinator. The data collection was based on a group discussion and semi-structured interview, which were interpreted in the light of André's Prose Analysis and were discussed based on three categories: teachers’ engagement and disengagement factors in the training moments (pedagogical coordination and teachers’ viewpoint); continuing education within the context-centered school; and collaborative work. The results point out that teachers perceive the importance of collective work in training as the best way to accomplish new learning and intervene in the reality of school; as well as to face challenges and find solutions working in a collaborative way, which produces feelings of belonging about what is being done. It emphasizes that reception, listening and dialogue are needs of the training environment and need to be part of work relationships to provide moments of reflection on the practice. This reflection comes from the comprehension of the school reality, and that, followed by a training project that makes sense to teachers, is capable of causing changes in their attitudes, beliefs and values, as long as they see positive results in the students' learning process. This work also presents, in its final considerations, notes for a teacher training concerned about collaborative performance between teachers and coordination